2007
DOI: 10.1016/j.urology.2007.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Disparity in Lower Urinary Tract Symptom Severity Between Community-Dwelling Non-Hispanic White, Mexican-American, and African-American Men

Abstract: Objectives-With significant differences in risks of renal failure in different ethnic/racial groups in the U.S., we sought to determine if disparities exist in reporting lower urinary tract symptoms (LUTS) in Non-Hispanic White (NHW), Mexican American (MA), and African American (AA) men. Epidemiological studies in AA men suggest they may have more LUTS compared to NHWs, but little is known about symptom prevalence among MA men.Methods-Data were collected from a prospective, community-based cohort assembled to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
2
2
Order By: Relevance
“…The oversampling of minorities in OAB‐POLL allowed for the prevalence of LUTS and OAB to be evaluated across the three largest racial/ethnic groups in the US. In contrast prior research showing that LUTS other than UI are similar across racial/ethnic groups,8–10 OAB‐POLL found statistically significant differences by racial/ethnic group for several LUTS among men and for a few LUTS among women. The prevalence of OAB was highest among AA men and women (20% and 33%).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The oversampling of minorities in OAB‐POLL allowed for the prevalence of LUTS and OAB to be evaluated across the three largest racial/ethnic groups in the US. In contrast prior research showing that LUTS other than UI are similar across racial/ethnic groups,8–10 OAB‐POLL found statistically significant differences by racial/ethnic group for several LUTS among men and for a few LUTS among women. The prevalence of OAB was highest among AA men and women (20% and 33%).…”
Section: Discussioncontrasting
confidence: 99%
“…Some research has evaluated the impact of racial/ethnic group on LUTS, UI,5–7 and OAB 8–10. While similar rates of LUTS have been found across racial/ethnic groups,8–10 UI has been shown to be more prevalent among white women compared with African‐American (AA) and Asian women,7, 11 and data on the prevalence of UI for Hispanic women in relation to other racial/ethnic groups are mixed 7, 12.…”
Section: Introductionmentioning
confidence: 99%
“…18,[22][23][24] It should also be mentioned here that, our observed prevalence was also higher than results obtained elsewhere in which IPSS tool was employed. 14,19,25 However, the prevalence in this present study was comparable to reports from hospital-based studies in south-western Nigeria (88.0%), Ethiopia (84.4%) and Port Harcourt, Nigeria (72.2%). 15,16,26 These observations tend to indicate that prevalence of LUTS suggestive of BPH in hospital-based studies is comparatively higher than that reported in population-based studies.…”
Section: Discussionsupporting
confidence: 83%
“…The estimate of 19.9% based on self-reported IPSS is comparable and in some cases higher than estimates from mostly white populations from France (12%), Germany (14%) and Canada (21%). 1315 However, our estimate for West African men was lower than those from studies using this same IPSS measure among African-American men in the United States, 7,10,11,17 which ranged from 26 to 45% (Table 3).…”
Section: Discussioncontrasting
confidence: 74%